Design of Pressure Measurement Instrument for Smart Footwear (Internetworking Indonesia Journal, 2020)
Walking, which is a type of gait, is a very common yet energetically demanding activity in daily life. In this study, we develop smart footwear to measure and record walking patterns which in the future may indicate the user’s health condition. The walking patterns are recorded by using several Force Sensing Resistor (FSR) sensors on the footwear. In this manuscript, we discuss the research to make a compressive force mechanism from the FSR pressure sensor to the computer as a stage for the development of the smart footwear. The compressive force is necessary to enable us to analyze the walking patterns. The study was performed in four stages. The first was manual measurement using a force gauge to apply force on the FSR pressure sensors. The second stage was making a simple Arduino circuit and program to detect the measurement. The third was making a voltage divider circuit to recognize the voltage on the sensor, accompanied by making a voltage detection program from the sensor. And the last stage was performing the main experiment followed by data analysis and report. The cftool MATLAB software was used to do curve-fitting and the Arduino software was needed for writing and uploading programs or code to the Arduino board and doing force measurements. The results show that the average minimum error is 3.4% and the maximum error is 25.9%. We also found that the largest error occurs at a force of 50 N, while the distribution of the smallest error occurs at 20 N. It seems that FSR pressure sensors have poor resistance to be applied to smart footwear. The problem may be solved by using better FSR sensors or simplifying the measurement, as well as by using a more sophisticated estimation such as Kalman filter.